ANALISIS PENGARUH KINERJA KEUANGAN BANK TERHADAP PERTUMBUHAN LABA (STUDI PADA BANK SWASTA DEVISA DI PASAR MODAL INDONESIA PERIODE 2013-2017) - Kusumasari, Indah; Kusuma, Desta Rizky (Jurnal Fokus Manajemen Bisnis, 2018)
The purpose of this study is to prove the Influence of Bank's Financial Performance on Profit Growth (Study on Foreign Exchange Private Banks in the Indonesian Capital Market for 2013-2017). The data used in this study were obtained from the Publication of Foreign Exchange Private Bank Financial Reports published in Financial Services Orientation with period 2013-2017. The total population of this study was 44 companies and the number of samples was 21 companies through the purposive sampling stage. The data analysis technique in this study uses panel data multiple regression analysis. Based on hypothesis testing using Partial Test (t), it concluded that Capital Adequacy Ratio (CAR) and Loan to Deposit Ratio (LDR) had no effect on the Growth of Profit, while Non-Performing Loans (NPL) and Operational Costs and Operating Income (BOPO) ) negative effect on Profit Growth (Growth).